2022
DOI: 10.1177/1045389x221121911
|View full text |Cite
|
Sign up to set email alerts
|

Review on single-phase driven ultrasonic motors

Abstract: In recent decades, various single-phase drive ultrasonic motors have emerged, and only a single excitation signal is used in their working states. Single-phase driven ultrasonic motors have the benefits of most ultrasonic motors, as well as the advantages of a simple driving circuit construction, low cost, high design flexibility, and high reliability, among others. According to the working principles, they are divided into three types: the vibration mode alternating type, the vibration mode coupling type, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…State-of-the-art piezoelectric motors can solve complex motion or positioning problems in different technological and scientific fields via high motion speed and resolution as well as compact size. Moreover, the advantages of piezoelectric motors, such as magnetic field-free operation, gear-free direct drive of loads, and self-locking abilities make these motors highly attractive compared to electromagnetic or other types of motion sources [ 21 , 22 ]. On the other hand, complex driving schematics, high operation frequencies, as well as these motors’ lack of direct integration abilities with small devices limit their application [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…State-of-the-art piezoelectric motors can solve complex motion or positioning problems in different technological and scientific fields via high motion speed and resolution as well as compact size. Moreover, the advantages of piezoelectric motors, such as magnetic field-free operation, gear-free direct drive of loads, and self-locking abilities make these motors highly attractive compared to electromagnetic or other types of motion sources [ 21 , 22 ]. On the other hand, complex driving schematics, high operation frequencies, as well as these motors’ lack of direct integration abilities with small devices limit their application [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicate that the proposed method is feasible. Xu et al [2] analyzed single-phase driven ultrasonic motors and found that single-phase ultrasonic motors have multiple advantages, which are of great significance for optimizing single-phase ultrasonic motors. Sun et al [3] proposed a new method for optimizing the load design of ultrasonic motors and constructed an experimental platform for testing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researches on lightweight and high energy density motors suitable for vacuum space with low temperature and strong pressure has always been a hot spot. As a new type of friction drive motor, ultrasonic motor has compact structure, rapid response and no electromagnetic interference when working [5][6][7]. These merits meet the needs of stable and reliable operation under complex and harsh working conditions, and have become a focus of attention in recent years.…”
Section: Introductionmentioning
confidence: 99%